The Impact of Social Media on Fear of Missing Out Among Z Generation: A Systematic Literature Review - Icha Herawati; Irfani Rizal; Nindy Amita (Journal of Islamic and Contemporary Psychology (JICOP), 2022)
Generation z is also known as the gadget generation. This generation lives side by side with the development of gadgets and social media. In this digital age, the use of social media is a way of life. Social media is unavoidable and is expected to have an effect on its users, the general picture of the current literature is missing. Therefore, the aim of this systematic is to summarize research on the impact of social media on fear of being out of date among Generation Z. Our systematic search on the Science and Scopus webs yielded 30 eligible articles. Gen z or generation z born between 1997 and 2003 (what), indicates that they will be between 18 and 24 in 2021. The use of social media and FOMO by generation z can be a negative and positive influence depending on their position and capacity. A negative example is that generation z is always desirable. They are shown that Generation Z is a tech-savvy generation. Based on these systematic results, it shows that the habit of using one of the social media has an impact on the fear of being left behind in generation z. The use of social media cannot be separated from the life of Generation Z. So FOMO is one of the characteristics of generation z that distinguishes it from other generations. Fomo is commonly used in marketing, industry, and lifestyle, where generation z is the main subject.